Robust control applied to power flow control in single-phase inverter with LCL filter, using droop control and D-stability - Sampaio, Leonardo P. [UNESP]; De Brito, Moacyr A. G. [UNESP]; Alves, Marcos G. [UNESP]; E Melo, Guilherme A. [UNESP]; Canesin, Carlos A. [UNESP] (Institute of Electrical and Electronics Engineers (IEEE), 2012)
This paper proposes a new methodology to control the power flow between a distributed generator (DG) and the electrical power distribution grid. It is used the droop voltage control to manage the active and reactive power. Through this control a sinusoidal voltage reference is generated to be tracked by voltage loop and this loop generates the current reference for the current loop. The proposed control introduces feed-forward states improving the control performance in order to obtain high quality for the current injected to the grid. The controllers were obtained through the linear matrix inequalities (LMI) using the D-stability analysis to allocate the closed-loop controller poles. Therefore, the results show quick transient response with low oscillations. Thus, this paper presents the proposed control technique, the main simulation results and a prototype with 1000VA was developed in the laboratory in order to demonstrate the feasibility of the proposed control. © 2012 IEEE.
Keywords: Active and Reactive Power; Closed loop controllers; Control performance; Control techniques; Current loop; Current reference; D stability; Distributed generators; Droop control; Electrical power; Feed-Forward; High quality; LCL filters; Power flow controls; Power flows; Single-phase inverters; Sinusoidal voltage; Voltage loops; Controllers; Distributed power generation; Industrial applications; Linear matrix inequalities; Robust control; Quality control